THE EFFECT OF BIBLIOTHERAPY ON ANXIETY LEVELS IN CHILDREN AT ANNISA TANGERANG HOSPITAL - Sari, Widia; Cahyani, Siti Meilinda; Pamungkas, Rian Adi; Karyanah, Yayah (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
ABSTRAK Hospitalisasi merupakan salah satu penyebab kecemasan pada anak usia sekolah. Umumnya terjadi peningkatan cemas pada anak akibat proses penyembuhan dan treatmen yang dijalani oleh anak. Salah satu yang didapat diberikan untuk mengurangi kecemasan pada anak usia sekolah adalah biblioterapi. Penelitian ini bertujuan untuk mengidentifikasi pengaruh biblioterapi terhadap tingkat kecemasan akibat hospitalisasi pada anak usia sekolah. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian pre eksperimen one group pre-test and post-test design. Sampel dalam penelitian ini adalah 39 responden. Hasil penelitian ini menunjukkan tingkat kecemasan sebelum dan sesudah diberikan intervensi biblioterapi dimana mean tingkat kecemasan sebelum adalah 3.95 dan setelah diberikan intervensi menjadi 1.28. Hasil uji statistic dengan paired sample t test didapat nilai p = 0,000 dengan CI 95% yang artinya ada pengaruh biblioterapi terhadap tingkat kecemasan anak di RS Annisa Tangerang. Oleh karena itu, pemberian biblioterapi direkomendasikan untuk diberikan pada anak usia sekolah yang sedang menjalani hospitalisasi. Kata kunci: Biblioterapi, kecemasan, hospitalisasi, anak usia sekolah Abstract Hospitalization can cause anxiety in school-age children. Children become increasingly anxious and this affects the healing process. For children who are hospitalized, to eliminate anxiety can be done using books as a therapeutic medium which is also called bibliotherapy. The research aims to identify the effect of bibliotherapy on anxiety levels of the effect of hospitalization on school-age children. This research is a quantitative study with a research design using the Pre-Experiment method and the research design used is a one group pre-test and post-test design with a sample of 39 respondents. The results showed the level of anxiety pre-test and post-test conducted biblioterapim intervention can be known that (mean) average level of anxiety before (pre-test) given bibliotherapy intervention of 3.95 (mean) average level of anxiety after (post -test) given biblioterpi intervention of 1.28. Hypothesis test results Paired Simple T-Test at a significance level of 95% (α = 0.05 indicates that the value of p value= 0,000) p value <α, ie 0,000 <0.05 means that Ho is rejected and Hₐ is accepted which indicates that there is an influence bibliotherapy on the anxiety level of the effect of hospitalization on school-age children in Tangerang an-nisa hospital in 2019. Suggestions are expected for hospitals to implement bibliotherapy interventions for children undergoing hospitalization. Keywords: Bibliotherapy, anxiety, hospitalization, school age children